2021
DOI: 10.3390/su131810241
|View full text |Cite
|
Sign up to set email alerts
|

Innovation as a Determinant of Growth in Outperforming Emerging Markets: An Analysis of South Korea

Abstract: Emerging economies and their speed of growth, competitiveness, and resilience are of great interest globally due to the high potential investors see in them. Innovation is one of the factors recognized to be the common ground of significantly outperforming economies. Therefore, identifying innovation benchmarks and how they impact economic success is relevant for a more straightforward evaluation of innovation in a country. This research focuses on the quantitative parts of innovation. Firstly, governmental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Iveco has been provided with parts and components to produce the armored vehicle while allowing complementary innovations to the platform, such as the RCWS and C2 systems. Promoting such relevant innovations help emerging economies grow globally [57].…”
Section: The Impact Of Actors and Interactions On Iesmentioning
confidence: 99%
“…Iveco has been provided with parts and components to produce the armored vehicle while allowing complementary innovations to the platform, such as the RCWS and C2 systems. Promoting such relevant innovations help emerging economies grow globally [57].…”
Section: The Impact Of Actors and Interactions On Iesmentioning
confidence: 99%
“…Yoon and Kwon (2022) gave competitiveness a technological dimension, measured by the number of patents. Patents issued in a country can be considered the result of investments in new and innovative ideas that contribute to economic success and growth (Hintringer et al, 2021).…”
Section: Patentsmentioning
confidence: 99%
“…Abt (2007) analyzed over 400,000 papers published over >30 years in the fields of physics, astronomy, geophysics, mathematics, and chemistry, showed that the publication rate of scientific papers depends only on the number of scientists and that there has been no increase in the average annual number of papers published per scientist in these fields. Hintringer et al (2021) showed that innovation, as measured by the number of patents, is strongly determined by the number of researchers. Phung et al (2019) showed that the number of researchers is relevant for the functioning of the science and innovation system and, through it for economic growth during 2006-2014 and involving data from 69 developed and developing countries.…”
Section: Researchersmentioning
confidence: 99%
“…Similarly, the number of energy researchers in a country has been shown to be a key determinant of a country's productivity in green innovation, with the number of patents correlated to the number of energy researchers (Yang et al 2022). A recent study in South Korea that compared the applicability of R&D investment, number of people with tertiary education, number of patents by non-citizens, number of patents by citizens, and researcher density found that the last two quanti able factors were better indicators of innovation (Hintringer et al 2021). Therefore, researcher density is used as an indicator of science, technology, and innovation (STI) development in the Sustainable Development Goals (SDG Indicator 9.5.2) and OECD members (OECD 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of researchers per million inhabitants (researcher density) is essential to meet global challenges (Hintringer et al 2021). This is probably because when many researchers address a common problem, they tend to differentiate themselves by searching for theories from other disciplines, which leads to the development of novel concepts, theories, and processes (Rothman et al 2001).…”
Section: Introductionmentioning
confidence: 99%